The relation of magnesium and calcium intakes and a genetic polymorphism in the magnesium transporter to colorectal neoplasia risk13 - Dai, Qi (2007)
BACKGROUND: Mean magnesium intake in the US population does not differ from that in East Asian populations with traditionally low risks of colorectal cancer and other chronic diseases, but the ratio of calcium to magnesium (Ca:Mg) intake is much higher in the US population. Transient receptor potential melastatin 7 (TRPM7) is a newly found gene essential to magnesium absorption and homeostasis. OBJECTIVE: We aimed to test whether the association of colorectal polyps with intake of calcium, magnesium, or both and Thr1482Ile polymorphism in the TRPM7 gene is modified by the Ca:Mg intake. DESIGN: Included in the study were a total of 688 adenoma cases, 210 hyperplastic polyp cases, and 1306 polyp-free controls from the Tennessee Colorectal Polyp Study. RESULTS: We found that total magnesium consumption was linked to a significantly lower risk of colorectal adenoma, particularly in those subjects with a low Ca:Mg intake. An inverse association trend was found for hyperplastic polyps. We also found that the common Thr1482Ile polymorphism was associated with an elevated risk of both adenomatous and hyperplastic polyps. Moreover, this polymorphism significantly interacted with the Ca:Mg intake in relation to both adenomatous and hyperplastic polyps. The subjects who carried ≥1 1482Ile allele and who consumed diets with a high Ca:Mg intake were at a higher risk of adenoma (odds ratio: 1.60; 95% CI: 1.12, 2.29) and hyperplastic polyps (odds ratio: 1.85; 95% CI: 1.09, 3.14) than were the subjects who did not carry the polymorphism. CONCLUSION: These findings, if confirmed, may provide a new avenue for the personalized prevention of magnesium deficiency and, thus, colorectal cancer.